THE IMPACT OF LEARNING DISCIPLINE AND LEARNING STYLES ON ACADEMIC ACHIEVEMENT - Asri, Karienda Faisa; Wibowo, Agus; Faslah, Roni (Faculty of Economics and Business, Universitas Negeri Jakarta, 2025)
This study was designed to investigate how learning discipline and learning styles function as predictors of academic achievement among vocational high school students in Indonesia. Employing a quantitative approach, the research involved 105 respondents selected through stratified probability sampling. Data were gathered through structured questionnaires and supporting documentation. All statistical computations were performed using SPSS 29. Learning discipline emerged as a strong predictor (p = 0.000) with a contribution of 32.1%, while learning style also showed a significant effect (p = 0.002) with a contribution of 16.4%. These results suggest that both variables partially affect student achievement. Simultaneously, the ANOVA test yielded p-value of 0.000 with a combined contribution of 38.3%, indicating that learning discipline and learning styles together exert a substantial influence on the academic achievement of Grade XI and XII Office Management students in the Human Resource Management subject at SMK Negeri 46 Jakarta. These insights underscore the need for schools to foster structured learning habits and accommodate diverse learning preferences to optimize student achievement.